Energy‐dependence investigation for a range of clinically used detectors from 70 kV to 6 MV. Issue 1 (30th November 2022) - Shields, Laura; Nikandrovs, Mihails; Vintró, Luis León; Clean, Brendan Mc
Abstract: Purpose: Accurate measurement of out‐of‐field dose in radiotherapy directly impacts beam data modeling in treatment planning systems, verification of implanted electronic devices/lens/fetus dose, secondary cancer risk estimation, and organ‐at‐risk dose reporting. When performing out‐of‐field dosimetry, it is therefore imperative that the response of the detector has been well characterized. Due to the softening of the radiation beam out‐of‐field, many detectors will exhibit energy dependence. This study investigated the energy dependence of a range of clinical available detectors over typical energies experienced out‐of‐field. Methods: The response of detectors to photon beams from 70 kV to 6 MV was measured. The relative change in response from 6 MV down to 70 kV highlighted the expected deviation in the response of detectors that would typically be calibrated in‐field for use out‐of‐field. Results: The Pinpoint detector displayed the most energy‐independent response over the energy range investigated. The Micro‐Lion detector was the only detector to show an under‐response to all low‐energy beams relative to 6 MV. The diode‐type detectors showed the largest energy dependence. Conclusions: When considering detectors for use in out‐of‐field dose measurements, it is important that the energy dependence is investigated over a low‐energy range as out‐of‐field the energy spectra comprise a larger component of photons in the 50–100‐keV range. This study highlights the variation in response of a range of clinically available detectors to low‐energy radiation beams relative to 6 MV for out‐of‐field dosimetry. The Pinpoint detector was the most energy‐independent detector with a response close to unity over the entire energy range investigated.